Maharashtra Rent Control Act 1999: unfinished agenda - Wadhva, Viran (2002)
In 1992, the government of India circulated a `model rent legislation' to state governments as a guide to reforming the state legislation in order to encourage investment in housing. Maharashtra is one of the four states that have evolved new rent legislation. What are its strengths and its inadequacies? - Reproduced.
Keywords: Maharashtra Rent Control Act, 1999; Housing - India - Maharashtra; Housing